PENGARUH PERCERAIAN ORANGTUA BAGI PSIKOLOGIS ANAK - Uswatun Hasanah (AGENDA: Jurnal Analisis Gender dan Agama, 2019)
The purpose of this paper is to know the effect of parental divorce on children's psychological. The method used qualitative research with a case study approach. The subject in this study amounted to one pair by using a purposive sampling technique that is sampling where the researcher has determined the criteria for the research subjects. The results of this study indicate that divorced parents will have a psychological effect on the child including the child receiving less attention, protection, and love from his father and mother.